NetShift: a methodology for understanding ‘driver microbes’ from healthy and disease microbiome datasets - Kuntal, B. K.; Chandrakar, P.; Sadhu, S.; Mande, S. S. (ISME Journal, 2019)
The combined effect of mutual association within the co-inhabiting microbes in human body is known to play a major role in determining health status of individuals. The differential taxonomic abundance between healthy and disease are often used to identify microbial markers. However, in order to make a microbial community based inference, it is important not only to consider microbial abundances, but also to quantify the changes observed among inter microbial associations. In the present study, we introduce a method called ‘NetShift’ to quantify rewiring and community changes in microbial association networks between healthy and disease. Additionally, we devise a score to identify important microbial taxa which serve as ‘drivers’ from the healthy to disease. We demonstrate the validity of our score on a number of scenarios and apply our methodology on two real world metagenomic datasets. The ‘NetShift’ methodology is also implemented as a web-based application available at